An Efficiency Analysis of Use of Recycled Lights - Siti Anisah; Rahmadhani Fitri; Rahmaniar Rahmaniar; Zutaidah Tharo (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Light bulb waste is one type of waste that is categorized into B3 waste which can cause environmental pollution, environmental pollution produced by waste and the absence of efficient handling methods is a problem currently faced by the government, especially non-organic waste which includes hazardous waste. and cannot be decomposed. Light bulb waste is included in the inorganic waste category, although the production of light bulb waste is still small, the waste has great potential for environmental pollution, so it is necessary to study environmental conservation efforts from this waste. Another problem is the potential for recycling waste light bulbs which is currently not fully utilized by the government and the public. The Innovation of Emergency Lighting Design based on Environmentally Friendly Technology (TRL) is a study to find out and analyze the results of recycling waste light bulbs into energy-efficient emergency lighting with the concept of Reduce, Reus, and Recycle to produce a product that can be reused. Research with analytical methods is carried out as an approach to the implementation of research. The analysis was carried out to find out the results of the field review data, besides that the analysis was also carried out from the electrical side in the form of measuring the electrical components contained in the light bulb so that it could support the success of the research. The results showed that recycled lighting can be implemented as an alternative lamp that is environmentally friendly.